ORGANISME PERUSAK KAYU PADA BEBERAPA RUMAH DI TIGA KABUPATEN DI PROPINSI JAWA BARAT - Ginuk Sumarni; Agus Ismanto (Jurnal Penelitian Hasil Hutan, 1989)
Survey on wood-destroying organisms attacking people's houses was carried out at Padalarang (Bandung district), Cibadak (Sukabumi districtj, and Pacet (Cianjur district). Data collection were done by interviewing and filling-out questionaire forms. Result of the investigation indicated that local timber and bamboo are used largely for house components. Wood destroying organisms found attacking the components are rotting fungi, subterranean termites, dry-wood termites, and powder post-beetles.